School and Work Status, Drug-Free Workplace Protections, and Prescription Drug Misuse Among Americans Ages 15–25 - Miller, Ted; Novak, S.; Galvin, D.; Spicer, R.; Cluff, L.; Kasat, S. (Alcohol Research Documentation, Inc Rutgers, 2015)
OBJECTIVE: We assessed the prevalence and characteristics of prescription drug misuse among youth ages 15-25 to examine differences by student and employment status, and associations with workplace antidrug policies and programs. METHOD: Multivariate logistic regressions analyzed associations in weighted data on the 20,457 young adults in the combined 2004-2008 National Surveys on Drug Use and Health. Demographic controls included sex, race, community size, and age group. RESULTS: After we accounted for demographic controls, at ages 15-25, students were less likely than nonstudents to misuse prescription drugs. Segmenting student from nonstudent groups, working consistently was associated with a further reduction in misuse for those ages 18-25. When we controlled for demographics and substance use history, both Employee Assistance Program (EAP) services and awareness that one's employer had a drug-free workplace policy were associated with significantly lower misuse of prescription drugs (OR = 0.85 for each program, 95% CI [0.73, 1.00] and [0.72, 1.00]). Associations of workplace antidrug policies and programs with marijuana use and with Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition, criteria for alcohol abuse and dependence contrasted sharply with these patterns. All four aspects were significantly associated with lower marijuana use. None was associated with problem drinking. CONCLUSIONS: Protective effects of drug-free workplace policy and EAPs persist after other substance use was controlled for. Comparing the effects of workplace programs on illicit drug use and problem drinking versus prescription misuse suggests that those protective associations do not result from selection bias. Thus, drug-free workplace policies and EAPs appear to help protect younger workers against prescription misuse. If workplace substance use disorder programs focused prevention messages and interventions on prescription drug misuse, their impact on misuse might increase.